Comparison of antibacterial efficacy of cinnamon extract, neem extract as irrigant and sodium hypochlorite against Enterococcus fecalis: An in vitro study - Veerale Panchal (Indian Journal of Dental Research, 2020)
Aim: The aim of the study is to compare the antibacterial effectiveness between cinnamon extract as irrigant with neem extract irrigant and sodium hypochlorite against E. fecalis. Materials and Methods: The present study is a randomized controlled in vitro study conducted on 60 extracted permanent single rooted teeth. The teeth were divided into three groups- Group 1 was irrigated with cinnamon extract, Group 2 was irrigated with neem extract irrigant and Group 3 with 3% sodium hypochlorite. The colonies in the reduction of E. feacalis was noted as CFU values per ml. Wilcoxon signed ranked test was used to compare in between the three groups. Mann- Whitney's test was used for inter group comparison between the three groups. Results: Cinnamon extract had the maximum reduction in the CFU colonies followed by sodium hypochlorite. Neem extract irrigant had the least reduction in the colonies of E. feacalis. (P < 0.05). Conclusion: Cinnamon extract irrigant show better reduction in E. fecalis as compared to 3% sodium hypochlorite and neem extract irrigant.